Identification Of Changes In Magnetic Clay Mineral Lattice Due To Batik Fabric Dyeing Process Using X-Ray Diffraction - Mardayani, Reza Sri; Rifai, Hamidi; Dwiridal, Letmi; Akmam, Akmam; Mufit, Fatni (INDONESIAN JOURNAL OF APPLIED PHYSICS, 2022)
Clay in West Sumatra has been developed as an industrial material, one of which is a natural dye for batik. The use of clay as a natural dye was previously known to have magnetic minerals contained in clay so as to produce color and resistance to fabrics. Currently, no one has investigated the types of magnetic minerals found in clay and their effect on color resistance in batik cloth, so this study aims to determine the types of magnetic minerals in clay and their effect on color resistance in batik cloth. Clay samples were taken from two areas in West Sumatra, namely Pesisir Selatan and Sijunjung. Samples were characterized from the extraction of clay using X-Ray Diffraction, where measurements were taken before and after the dyeing process on the fabric. The results showed that the types of magnetic minerals found in the clay before and after dyeing the fabric were Maghemite. In addition, the non-magnetic mineral found in clay is Quartz. The color resistance test on the CL-SPPS-210314-2 fabric sample did not change color, on the contrary, the CL-PSBSJJ-210421 fabric sample experienced quite a change from the original color of the fabric or before washing.